Antiseizure drugs and risk of developing smoking‐related chronic obstructive pulmonary disease or lung cancer: A population‐based case–control study. Issue 3 (30th August 2020) - Leuppi‐Taegtmeyer, Anne B.; Reinau, Daphne; Yilmaz, Stella; Rüegg, Stephan; Krähenbühl, Stephan; Jick, Susan S.; Leuppi, Jörg D.; Meier, Christoph R.
Abstract : Aims: To determine whether enzyme‐inducing antiseizure drugs (ASDs) affect the risk of developing chronic obstructive pulmonary disease (COPD) or lung cancer in smokers. Methods: Cases of COPD and lung cancer and matched controls without these conditions were identified from a population of smokers with ≥1 prescription for any type of ASD in the Clinical Practice Research Datalink UK database of patients managed in primary care (1995–2016). A matched case–control study was performed utilising multivariate logistic regression analyses of exposure to enzyme‐inducing ASDs compared to non–enzyme‐inducing ASDs. The duration of ASD exposure and level of tobacco exposure were also assessed. Results: We identified 5952 incident COPD and 1373 incident lung cancer cases, and 59 328 and 13 681 matched controls, respectively. Compared with never use, ever use of enzyme‐inducing ASDs was associated with slightly decreased risk estimates of COPD (adjusted odds ratio: 0.85, 95% confidence interval: 0.81–0.89) and lung cancer (adjusted odds ratio: 0.82, 95% confidence interval: 0.73–0.92). These risk estimates were attenuated in heavy smokers. Conclusion: We found slightly decreased risk estimates of COPD and lung cancer among smokers taking enzyme‐inducing ASDs and hypothesise that this may be related to induction of detoxification of tobacco‐specific lung toxins.